Analisis Potensi Wisata Taman Laut Olele Di Kecamatan Kabila Bone Kabupaten Bone Bolango - Amas, Wahydin S; Eraku, Sunarty S; Kobi, Wiwin (-, 2025)
This research aims to analyze the tourism potential of the marine park in Olele Village to be feasibly developed as a tourist attraction in Bone Bolango Regency. This is qualitative research, also known as the naturalistic method, because the research is conducted in natural conditions. It is often also called the interpretive method because the research data is more related to interpreting the data found in the field. The data analysis technique used is the Analysis of Operational Areas of Natural Tourism Objects and Attractions of the Directorate General of PHKA (Forest Protection and Nature Conservation) in 2003. Based on the assessment of object and attractions, the marine park tourism area has a percentage value of 85.9%. The marine park tourism attractions criteria have a percentage value of 90%. While the accessibility criteria have the lowest percentage value of 77.8%. supporting facilities and infrastructure have a feasibility level of 90%, so they are categorized as worth developing. Based on the results of research and discussion, it can be concluded that marine park tourism is worth developing as one of the tourist destinations